Keberhasilan Pelaksanaan Senam Hamil terhadap Proses Persalinan - vitri yuli afni amran (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The American College of Obstetricians and Gynecologists (ACOG) recommends exercise as a preventive measure for mothers so that the process of pregnancy and childbirth runs naturally and reduces the crisis caused by childbirth. This study aims to determine the analysis of the success rate of the implementation of pregnant exercise on the delivery process at the Puskesmas Lubuk Buaya Padang in 2018. This type of research is an analytical study with a cross-sectional approach that has been carried out in the Work Area of ??the Lubuk Buaya Puskesmas in Padang in October 2017 - June. 2018. The population of all mothers who have experienced childbirth in the Lubuk Buaya Padang Public Health Center is 2,042 people. Samples were taken by simple random sampling with a total sample of 48 people. Data collection using a questionnaire. Then the data were analyzed by univariate and bivariate with the chi-square statistical test. The results showed that 31.3% of mothers did not carry out pregnancy exercise correctly. As much as 37.5% of mothers gave birth with action and based on bivariate analysis there was a significant relationship between the success rate of implementing pregnancy exercise and the delivery process (p = 0.000). The results of the study, it can be concluded that there is a relationship between the success rate of implementing pregnancy exercise with the delivery process, it is hoped that health workers will continue to provide health education and counseling and disseminate information about pregnancy exercise and empower other health workers to conduct pregnancy exercise counseling for pregnant women. how to demonstrate every pregnancy exercise movement in various pregnancy class activities so that mothers can understand it. Key words: pregnancy exercise, childbirth process, class of pregnant women